E0065 The association between the single nucleotide polymorphisms of matrix metalloproteinases and the carotid atherosclerosis in patients with essential hypertension. (17th November 2010) - Ma, Yan-Ping; Xu, Xin-Juan; Zhao, Fang; Hu, Guang-Mei; Zhang, Jun-Shi
Abstract : Objective: To investigate the relationship between the single nucleotide polymorphisms (SNP) of matrix metallo proteases (MMP-2 -735C/T; MMP-3 -1171 5A/6A) and the carotid atherosclerosis (CAS) in Chinese Han and Uygur populations with EH. Methods: The study comprised 276 Han nationality and 212 Uygur participants, who were divided into two groups: CAS (n=293) and NS (n=195). Genotypes were detected by PCR-RFLP and their frequencies were determined. Results: (1) The frequencies of MMP-2 TT genotype and T allele in CAS were higher than in NS (Han : X 2 =11.441, p=0.003; Uygur : X 2 =28.255, p=0.000). In NS, the frequencies of TT genotype and T allele in Han were higher than in Uygur (X 2 =12.509, p=0.001)). (2) The frequencies of MMP−3 6A/6A genotype and 6A allele in CAS were higher than NS (Han: X 2 =7.523, p=0.024; Uygur: X 2 =6.474, p=0.039). The frequencies of MMP−3 6A/6A genotype and 6A allele in Han were higher than Uygur (CAS: X 2 =26.230, p=0.000; NS: X 2 =18.809, p=0.000). (3) The single gene analysis showed Han individuals with CT or TT genotypes had 2.25-fold risk and Han individuals with 6A/6A genotypes had 1.85-fold risk suffering from CAS. Han individuals with both T allele and 6A/6A genotypes had 3.17-fold risk suffering from CAS. The single gene analysis showed that Uygur individuals with CT or TT genotypes had 5.04-fold risk suffering from CAS. Uygur individuals with 6A/6A genotypes had 2.20-fold risk suffering from CAS. Uygur individuals with both T allele and 6A/6A genotypes had 3.20-fold risk suffering from CAS. (4)According to MMP-2 genetypes, Han individuals with MMP-2 CT+TT genotypes had higher LDL and lower HDL levels than CC genotype in CAS (LDL:2.9 mmol/l vs 2.6 mmol/l; HDL:1.2 mmol/l vs mmol/l). Uygur individuals with CT+TT genotypes had higher TG levels than CC genotype (CAS : 2.5 mmol/l vs 1.6 mmol/l; NS : 3.9 mmol/l vs 2.0 mmol/l). According to MMP−3, Han individuals with 6A/6A genotype had higher T-CHOL and LDL levels than 5A/5A+5A/6A genotypes in NS group (T-CHOL : 4.6 mmol/l vs 4.2 mmol/l; LDL: 2.3 mmol/l vs 2.2 mmol/l). (5) The binary logistic regression analysis showed MMP-2 CT+TT genetypes were the risk factors for CAS in individuals with EH (Uygur: OR=9.65; Han : OR=2.076). MMP-3 6A homogeneses were the risk factors for CAS in Han individuals with EH (OR=1.802). MMP-2 CT+TT and MMP-3 6A homogeneses had a combined influence on the incidence of CAS in Han individuals with EH. Conclusions: (1) Han and Uygur individuals had differential distribution of MMPs. (2) The SNP of MMP-2 -735C/T is associated with CAS in individuals with EH. The MMP-2 T allele may be a risk factors on CAS in individuals with EH. The SNP of MMP-3 -1171 5A/6A is associated with CAS in Han individuals with EH. The 6A allele may be a risk factors on CAS in Han individuals with EH.